Heteroepitaxial fabrication and structural characterizations of ultrathin GaN nanotube arrays - An, Sung Jin (Journal of the Korean Physical Society, 2012)
We report on the heteroepitaxial fabrication and the structural characterizations of ultrafine GaN nanotube arrays. The ultrathin GaN nanotube arrays were fabricated by using epitaxial growth of a ultrathin GaN layer on ZnO nanoneedles and etching core Zno nanoneedles. Epitaxial growth of GaN and precise etcing control of core ZnO nanoneedles were obtained by using low-pressure metalorganic vapor-phase epitaxy. ZnO nanoneedles were grown on Si and sapphire substrates by using catalyst-free metal-organic chemical vapor deposition. Furthermore, the structural properties of the nanostructures were investigated using both synchrotron-radiation X-ray diffraction and highresolution transmission electron microscopy. The strain induced during the GaN deposition on ZnO was nearly sustained even after the removal of core ZnO.